Risk governance and regulatory adjustments in the public commercial banks of OECD - Malik, Muddassar (Emerald Publishing, 2025)
Purpose
This study aims to explore the relationship between risk governance characteristics (chief risk officer [CRO], chief financial officer [CFO] and senior directors [SENIOR]) and regulatory adjustments (RAs) in Organization for Economic Cooperation and Development public commercial banks.
Design/methodology/approach
Using principal component analysis (PCA) and regression models, the research analyzes a representative data set of these banks.
Findings
A significant negative correlation between risk governance characteristics and RAs is found. Sensitivity analysis on the regulatory Tier 1 capital ratio and the total capital ratio indicates mixed outcomes, suggesting a complex relationship that warrants further exploration.
Research limitations/implications
The study’s limited sample size calls for further research to confirm findings and explore risk governance’s impact on banks’ capital structures.
Practical implications
Enhanced risk governance could reduce RAs, influencing banking policy.
Social implications
The study advocates for improved banking regulatory practices, potentially increasing sector stability and public trust.
Originality/value
This study contributes to understanding risk governance’s role in regulatory compliance, offering insights for policymaking in banking.